Early Developmental Exposure to Fluoxetine and Citalopram Results in Different Neurodevelopmental Outcomes. (15th July 2021) - Liu, Karine; Garcia, Alfonso; Park, Jenn J.; Toliver, Alexis A.; Ramos, Lizmaylin; Aizenman, Carlos D.
Abstract: Although selective serotonin reuptake inhibitors are commonly prescribed for prenatal depression, there exists controversy over adverse effects of SSRI use on fetal development. Few studies have adequately isolated outcomes due to SSRI exposure and those due to maternal psychiatric conditions. Here, we directly investigated outcomes of exposure to widely-used SSRIs Fluoxetine and Citalopram on the developing nervous system of Xenopus laevis tadpoles, using an integrative experimental approach. We exposed tadpoles to low doses of Citalopram and Fluoxetine during a critical developmental period and found that different experimental groups displayed opposing behavioral effects. While both groups showed reduced schooling behavior, the Fluoxetine group showed increased seizure susceptibility and reduced startle habituation. In contrast, Citalopram treated tadpoles had decreased seizure susceptibility and increased habituation. Both groups had abnormal dendritic morphology in the optic tectum, a brain area important for behaviors tested. Whole-cell electrophysiological recordings of tectal neurons showed no differences in synaptic function; however, tectal cells from Fluoxetine-treated tadpoles had decreased voltage gated K+ currents while cells in the Citalopram group had increased K+ currents. Both behavioral and electrophysiological findings indicate that cells and circuits in the Fluoxetine treated optic tecta are hyperexcitable, while the Citalopram group exhibits decreased excitability. Taken together, these results show that early developmental exposure to SSRIs is sufficient to induce neurodevelopmental effects, however these effects can be complex and vary depending on the SSRI. This may explain some discrepancies across human studies, and further underscores the importance of serotonergic signaling for the developing nervous system.